The “Fountain of Death”: A Case Series on Tracheo-innominate Artery Fistula - Lo, Jason; Mat Baki, Marina; Yi , Yeoh Xing; Amirul , Nik Hisyam; Zakaria , Zahirrudin (IIUM Medical Journal Malaysia, 2021)
Tracheo-innominate artery fistula (TIF) is a very rare complication related to tracheostomy and has been reported in 0.7% of patients, but certainly is one of the most life-threatening conditions. It is of paramount importance to maintain a high index of suspicion in evaluating patients with TIF and to anticipate occurrence of massive haemorrhage even during simple procedures related to tracheostomy such as tube change. We report 3 cases of TIF, each with a unique and unsuspecting history of the condition and review the emergency protocol in arresting the bleeding. We’ve also highlighted the potential role of permissive hypotension with sedation in improving survival outcomes of patients with TIF.